Bibliometric Analysis of Augmented Reality Research in Medicine - Adimart Permana, Andhika Solihan Asbi; Lukito, Aryo (Westscience Press, 2024)
This study aims to carry out a bibliometric analysis of the studies that have been carried out related to Augmented Reality (AR) in particular in the field of medicine. Augmented reality technology, which is becoming increasingly popular in the field of medicine, has the potential to improve medical diagnosis, treatment, and training. In this research, we perform bibliometric analysis of relevant scientific publications published in a particular period. Bibliometric analysis methodology gathers data on AR research in the field of medicine. This includes the title, author, journal where it was published, year of publication, and keyword used. The results of bibliometric analysis showed rapid progress in AR research in the field of medicine. In the last five years (2018-2023), as many as 250 publications were selected based on research criteria. This analysis reaches the conclusion that research on AR in the field of medicine is vital and increasingly recognized in the scientific community. The results of this analysis can help researchers and medical practitioners understand current trends with the use of AR in medical practice.